Private Participation in the Water and Sewerage Sector : Recent Trends - Silva, Gisele; Tynan, Nicola; Yilmaz, Yesim (World Bank, Washington, DC, 2012)
The PPI (Private Participation in Infrastructure) Project Database covers private participation in infrastructure in developing countries. The database records details of all projects owned or managed by private companies in 1984-97 in the water, energy, transport, and telecommunications sectors. This Note focuses on private water and sewerage projects that reached financial closure between 1990 and 1997 and surveys regional trends, type of private participation, project size, and top sponsors and operators. The PPI Database reveals the following trends in private participation in water and sewerage: a) a regional and national concentration of private water projects, reflecting varied government efforts to create conditions for sustainable private involvement through pricing, regulatory, and institutional reforms, but also a ripple effect from growing government familiarity with private involvement in the sector; b) a dominance of concession contracts compared with divestitures, BOT (build, operate, transfer) contracts, leases, and, management contracts; and c) a few international companies sponsoring and operating most major projects.